2023
DOI: 10.1007/s11356-023-25701-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood mercury levels with bone mineral density in adolescents aged 12–19

Abstract: Adolescence is a critical period of rapid bone mass growth, and achieving higher bone mineral density (BMD) during this period can help prevent osteoporosis. The effects of metallic mercury on bone health remain unclear and controversial. Numerous studies have focused on perimenopausal women and older adults, and the association of blood mercury with bone mineral density in adolescents has not been discussed. This study aimed to collect data from the National Health and Nutrition Examination Survey (NHANES) 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…A study on adolescents aged 12-19 found that blood mercury levels were signi cantly related to bone density in adolescents. Inverse correlation (Xu et al, 2023), consistent with another study based on the US NHANES database, there is a negative correlation between blood mercury levels and spinal bone density in adults, with low blood mercury levels (< 3 ug/L) having increased osteoporosis risk (Tang et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…A study on adolescents aged 12-19 found that blood mercury levels were signi cantly related to bone density in adolescents. Inverse correlation (Xu et al, 2023), consistent with another study based on the US NHANES database, there is a negative correlation between blood mercury levels and spinal bone density in adults, with low blood mercury levels (< 3 ug/L) having increased osteoporosis risk (Tang et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…All covariates included and adjusted in this study were collected based on prior literature [25][26][27][28][29], including age, gender, race, poverty income ratio, body mass index (BMI), physical activity, total calcium, phosphorus, total protein, and total cholesterol. BMI was calculated as measured weight (kg) divided by the square of height (m 2 ) and divided into underweight, normal, overweight, and obese according to the Centers for Disease Control and Prevention's sex-specific 2000 BMI-for-age growth charts for the United States [30].…”
Section: Covariatesmentioning
confidence: 99%